Early pregnancy prediction of gestational diabetes mellitus risk using prenatal screening biomarkers in nulliparous women. (May 2020) - Snyder, Brittney M.; Baer, Rebecca J.; Oltman, Scott P.; Robinson, Jennifer G.; Breheny, Patrick J.; Saftlas, Audrey F.; Bao, Wei; Greiner, Andrea L.; Carter, Knute D.; Rand, Larry; Jelliffe-Pawlowski, Laura L.; Ryckman, Kelli K.
Highlights: Identifying women at risk for gestational diabetes early in pregnancy is ideal. Prenatal screening biomarkers may be of value in screening for gestational diabetes. To assess clinical utility, risk stratification and reclassification were performed. No net classification improvement indicated limited clinical utility of biomarkers. Utility of other biomarkers in predicting gestational diabetes risk is warranted. Abstract: Aims: To evaluate the clinical utility of first and second trimester prenatal screening biomarkers for early pregnancy prediction of gestational diabetes mellitus (GDM) risk in nulliparous women. Methods: We conducted a population-based cohort study of nulliparous women participating in the California Prenatal Screening Program from 2009 to 2011 (n = 105, 379). GDM was ascertained from hospital discharge records or birth certificates. Models including maternal characteristics and prenatal screening biomarkers were developed and validated. Risk stratification and reclassification were performed to assess clinical utility of the biomarkers. Results: Decreased levels of first trimester pregnancy-associated plasma protein A (PAPP-A) and increased levels of second trimester unconjugated estriol (uE3 ) and dimeric inhibin A (INH) were associated with GDM. The addition of PAPP-A only and PAPP-A, uE3, and INH to maternal characteristics resulted in small, yet significant, increases in area under the receiver operating characteristic curve (AUC) (maternal characteristics only: AUC 0.714 (95% CI 0.703–0.724), maternal characteristics + PAPP-A: AUC 0.718 (95% CI 0.707–0.728), maternal characteristics + PAPP-A, uE3, and INH: AUC 0.722 (0.712–0.733)); however, no net improvement in classification was observed. Conclusions: PAPP-A, uE3, and INH have limited clinical utility for prediction of GDM risk in nulliparous women. Utility of other readily accessible clinical biomarkers in predicting GDM risk warrants further investigation.